38th Plasmadynamics and Lasers Conference 2007
DOI: 10.2514/6.2007-4595
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Studies of Low-Temperature M=4 Flow Deceleration by Lorentz Force

Abstract: The paper presents results of cold MHD flow deceleration experiments using repetitively pulsed, short pulse duration, high voltage discharge to produce ionization in a M=4 nitrogen flow in the presence of transverse DC electric field and transverse magnetic field. Effective flow conductivity is significantly higher than was previously achieved, σ eff =0.1 S/m. MHD effect on the flow is detected from the flow static pressure measurements. Retarding Lorentz force applied to the flow produces a static pressure in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Nishihara et al [16] detected low temperature supersonic air flow deceleration by Lorentz force from the static pressure measurements. Rawat et al [17] performed 3D compressible Navier-Stokes MHD simulations and showed results of flow deceleration consistent with Nishihara et al [18,19].…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Nishihara et al [16] detected low temperature supersonic air flow deceleration by Lorentz force from the static pressure measurements. Rawat et al [17] performed 3D compressible Navier-Stokes MHD simulations and showed results of flow deceleration consistent with Nishihara et al [18,19].…”
supporting
confidence: 55%
“…Hunt and Leibovich [13] focused on high magnetic interaction parameters and Hartmann numbers but low magnetic Reynolds-number effects on variable cross-section channel flows, which are decelerated by transverse magnetic fields. More recent work focused on flow control prospects of transverse magnetic fields on channel flows [14][15][16][17][18]. Macheret et al [14] studied the scramjet inlet flow control by applying an MHD system upstream of the inlet and showed that, with reasonable parameters, shocks could be brought back to the cowl lip when flying at off-design Mach numbers.…”
mentioning
confidence: 98%
“…One current channel flow system has been configured to place an accelerating or retarding force on a high-speed flow (Mach 3.0-4.0) of air or another mixture of gases. 12,23,[27][28][29][30][31][32][33][34][35][36][37] The test section pressure is limited to 7-20 torr. 27 The gas is transformed into a weakly ionized gas (WIG) by means of a high voltage, high frequency electric field pulse circuit.…”
Section: Channel Flow and Open Flow Experimentationmentioning
confidence: 99%
“…With slightly different test section conditions, a current oscillogram appears in Ref. 37 for an ionization frequency of 100 kHz, which results in a steadier Lorentz force because the WIG decays less. As one can see from Fig.…”
Section: American Institute Of Aeronautics and Astronauticsmentioning
confidence: 99%